HUBUNGAN ADVERSITY QUOTIENT DENGAN CAREER ADAPTABILITY PADA KOAS ANGKATAN 2015 FKG “X” DI RSGM - Yoga Hardianto; Rizka Bella Sucihayati (Psibernetika, 2018)
ABSTRACT: This study originated from the lack of research linking adversity quotient with career adaptability. One study found that there was a positive correlation between adversity quotient and career adaptability. The purpose of this research is to know empirically the correlation between adversity quotient with career adaptability in the Coas class of 2015 FKG “X” at RSGM. This research is a quantitative research with correlational research and deductive approach. The number of samples is 65 people and using probability sampling technique is total population sampling. The measuring instrument used is the Adversity Quotient Questionnaire compiled by the researcher based on Paul Stoltz's (2000) theory with the reliability test result is 0.885 and the validity test result is 0.400-0.667 and career adaptability measurements using the Career Adapt-Ability Scale developed by Savickas et. al (2012) with the result of the reliability test is 0.955 and the result of the validity test is 0.404-0.906. Based on the results of hypothesis testing using the Spearman’s rho correlation matrix method, there is a significant positive relationship between Adversity Quotient and Career Adaptability in the moderate category (r = 0.580). This means that the higher the Adversity Quotient possessed by Koas, the higher the Career Adaptability. As for suggestion for RSGM is to pay more attention to Coas belonging to Campers and Quitters, and also to those who have low Career Adaptability levels.Keywords: Adversity Quotient, Career Adaptability.ABSTRAK: Penelitian ini berawal dari sedikitnya penelitian yang menghubungkan adversity quotient dengan career adaptability. Salah satu penelitian menemukan bahwa terdapat hubungan positif antara adversity quotient dengan career adaptability. Tujuan dari penelitian ini adalah untuk mengetahui secara empiris hubungan adversity quotient dengan career adaptability pada Koas Angkatan 2015 FKG “X” di RSGM. Penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian correlational research dan pendekatan deduktif. Jumlah sampel sebanyak 65 orang dan menggunakan teknik sampel probability sampling yaitu total population sampling. Alat ukur yang digunakan adalah instrumen Adversity Quotient yang disusun oleh peneliti berdasarkan teori Paul Stoltz (2000) dengan hasil uji reliabilitas 0,885 dan hasil uji validitas 0,400-0,679 dan pengukuran career adaptability menggunakan Career Adapt-Ability Scale yang dikembangkan oleh Savickas et. al (2012) dengan hasil uji reliabilitas 0,955 dan hasil uji validitas 0,404-0,906. Berdasarkan hasil dari pengujian hipotesis dengan menggunakan metode correlation matrix spearman’s rho terdapat hubungan positif yang signifikan antara Adversity Quotient dengan Career Adaptability dengan kategori sedang (r= 0,580) Artinya, semakin tinggi Adversity Quotient yang dimiliki oleh Koas maka semakin tinggi pula Career Adaptability-nya. Adapun saran untuk RSGM untuk lebih memperhatikan Koas yang tergolong Campers dan Quitters, juga yang memiliki tingkat Career Adaptability yang rendah.Kata Kunci: Adversity Quotient, Career Adaptability .